2010
DOI: 10.3390/d2010072
|View full text |Cite
|
Sign up to set email alerts
|

Origin and Domestication of Native Amazonian Crops

Abstract: Molecular analyses are providing new elements to decipher the origin, domestication and dispersal of native Amazonian crops in an expanding archaeological context. Solid molecular data are available for manioc (Manihot esculenta), cacao (Theobroma cacao), pineapple (Ananas comosus), peach palm (Bactris gasipaes) and guaraná (Paullinia cupana), while hot peppers (Capsicum spp.), inga (Inga edulis), Brazil nut (Bertholletia excelsa) and cupuassu (Theobroma grandiflorum) are being studied. Emergent patterns inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
258
2
47

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 349 publications
(312 citation statements)
references
References 86 publications
5
258
2
47
Order By: Relevance
“…123 Temporal and geographical information comes from Pearsall 124. , Clement et al 125 130 . 131 have shown that the area that our figure shows was subject to intensive land use for several centuries between the 8 th and 12 th centuries CE, punctuated by episodes of severe erosion.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…123 Temporal and geographical information comes from Pearsall 124. , Clement et al 125 130 . 131 have shown that the area that our figure shows was subject to intensive land use for several centuries between the 8 th and 12 th centuries CE, punctuated by episodes of severe erosion.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Por exemplo, no império andino Wari (600-1100 d.C.), o uso de um vegetal alternativo ao milho, fruto da árvore Schinus molle, teria sido um diferenciador desse grupo Figura 2 -Vaso Jívaro para a preparação (acima) e consumo de cerveja (demais) Fonte: Karsten, 1935. Figura 1 -Vasos Guarani para preparo e consumo de fermentados Foto Stephen Shennan/Museu de Arqueologia do Rio Grande do Sul em relação aos demais (Goldstein et al, 2009). O que, até certo ponto, pode ter ocorrido na região do alto Madeira, onde alguns grupos optaram pela utilização da mandioca, ali domesticada (Clement, 1999;Clement et al, 2010;Olsen;Schaal, 1999), outros pelo milho, introduzido de fora (por migrantes Arawak? ), assim como outros vegetais e outras combinações.…”
Section: Cerâmicas Etílicasunclassified
“…Segundo esses autores, há vários e importantes estudos sobre a diversidade genotípica e fenotípica de espécies arbóreas ou lenhosas na Amazônia focados em processos de domesticação de plantas e de paisagens por sociedades locais, entre os quais se incluem espécies como a castanheira-do-brasil (Bertholletia excelsa), a pupunha (Bactris gasipaes), o cacau (Theobroma cacao) e o guaraná (Paullinia cupana var. sorbilis) (Clement et al, 2010(Clement et al, , 2009b. Contudo, há ainda poucos estudos centrados na 'dimensão sociocultural' do cultivo e na domesticação local de espécies arbóreas, sobretudo no contexto de sistemas agrícolas indígenas.…”
Section: Introductionunclassified